Regina Galasso & Evelyn Scaramella, eds. Avenues of Translation: The City in Iberian and Latin American Writing. Bucknell UP, 2019. - Enric Mallorqui-Ruscalleda (Studies in 20th & 21st Century Literature, 2019)
Review of Regina Galasso & Evelyn Scaramella, eds. Avenues of Translation: The City in Iberian and Latin American Writing. Bucknell UP, 2019.
Keywords: translation; Spain; Latin America; urban; city